From tweets to power: an integrative thematic review of political communication and platform governance on Twitter/X (2009–2024) - Naranjo-Vinueza, Andrés; Casillas-Martín, Sonia; Cabezas-González, Marcos; Nevado-Batalla Moreno, Pedro T. (Frontiers in Political Science, 2025)
IntroductionThis integrative thematic review synthesizes the body of peer-reviewed studies on political communication via Twitter/X, aiming to map the conceptual and methodological landscape of the field as indexed in major databases from the platform’s inception in 2009 through 2024.MethodsThe review followed a PRISMA-style workflow for search, de-duplication, and screening, resulting in a final corpus of 52 articles from the Web of Science Core Collection and Scopus. Included studies were analyzed using a hybrid deductive-inductive thematic analysis.ResultsFindings are organized around five central themes: (1) actor strategy (personalization, timing, campaign orchestration), (2) audience behavior (engagement patterns, selective exposure), (3) platform architecture (affordances, algorithmic mediation), (4) trust and legitimacy (institutional credibility vs. visibility logics), and (5) methodological innovation (computational scaling vs. interpretive depth). The analysis reveals conceptual consolidation but also a structural imbalance in the field, characterized by the dominance of US and EU scholarship, limited cross-regional integration, and uneven theoretical convergence.DiscussionThe study argues for three key developments in future research: the adoption of mixed-method designs integrating discourse, network, and behavioral data; greater attention to non-Western contexts; and the explicit treatment of platforms as political actors, not just communication stages. Limitations include the restriction to two databases and a specific timeframe, the absence of a formal quality appraisal, and evolving platform conditions that challenge reproducibility. This review provides a roadmap for building more cumulative, comparative, and theory-driven research on the intersection of Twitter/X and governance.